Natural antidepressants in neuroimmunomodulation: molecular mechanisms, action targets, and therapeutic potential - Lv, Shimeng; Kong, Linghui; Zhong, Xia; Shang, Ruirui; Lu, Yitong; Zhang, Guangheng; Gao, Haonan; Hou, Xin; Li, Guoqiang; Yu, Xiaowen (Frontiers in Immunology, 2025)
Depression is a major global public health issue, yet key bottlenecks remain in understanding its pathophysiological mechanisms, which significantly hinder breakthroughs in precision treatment strategies. Recent studies have highlighted the neuroimmune system as a primary pathogenic contributor to the onset and progression of depression. Meanwhile, natural products, characterized by multi-component synergy, multi-target activity, and multi-pathway regulation, have shown significant potential in regulating neuroimmunity. However, a systematic review of the role of neuroimmunity in the pathological process of depression and the therapeutic effects of natural products is still lacking. This review aims to comprehensively elucidate the core role of neuroimmunity in the pathological mechanisms of depression through literature analysis, explore in depth the molecular mechanisms and targets involved in natural product interventions, and critically evaluate the limitations and current challenges in clinical translation. Ultimately, this review provides a solid theoretical foundation and guidance for future research and the development of precision antidepressant therapies based on natural products.